The Construction of Contemporary Maqasid: A Paradigm Shift from Textual to Contextual Approaches - Azwarfajri, Azwarfajri; Sa'dan, Saifuddin; Zakaria, Syahminan; Yusuf, Muhammad (Jurnal Pemikiran Islam, 2025)
This study examines the epistemological reconstruction of maqashid al-sharī‘ah as a contemporary methodological framework for Islamic legal derivation in response to the increasing complexity of modern socio-legal realities. While classical Islamic jurisprudence traditionally relied on scriptural texts (naṣṣ) and analogical reasoning (qiyās), the rapid transformation of social, political, economic, and technological structures necessitates a more adaptive and purposive approach to legal reasoning. Through qualitative library research supported by normative and conceptual analysis, this study explores the historical evolution of maqashid al-sharī‘ah, beginning with its classical formulation by figures such as al-Juwaynī, al-Ghazālī, and al-Shāṭibī, and its subsequent reformulation by contemporary scholars including Jasser Auda, Ibn Bayyah, and Yusuf al-Qarḍāwī. The findings reveal a paradigmatic shift from an essentialist and text-oriented interpretation of maqashid toward a contextual, systemic, and value-oriented framework that integrates inductive–deductive reasoning, social analysis, and public welfare considerations. This contemporary maqashid paradigm not only expands the al-kulliyyāt al-khamsah but also incorporates broader dimensions such as human rights, gender justice, environmental sustainability, and good governance. As a methodological tool, contemporary maqashid strengthens the relevance of Islamic law in addressing modern legal challenges by harmonizing the relationship between text, context, and legal purpose. The study concludes that reconstructing maqashid into a dynamic legal methodology provides an effective means to bridge the tension between immutable scriptural principles and evolving human realities, thereby enabling Islamic law to function as an ethical, justice-oriented, and welfare-driven system aligned with the universal spirit of a mercy for all creation (raḥmatan lil ‘ālamīn).